Transparent weather-resistant glass fiber reinforced thermoplastic-based composite material and preparation method thereof
Combining polyadipyl isophthalamine by melt blending and hot pressing of polyethylene terephthalate and polyethylene isophthalate in glass fiber reinforced thermoplastic composites and compatibility agents solve the problems of opacity and mechanical properties of materials, and achieve transparent weathering glass fiber reinforced thermoplastic composite materials with high light transmittance and excellent mechanical properties.
Patent Information
- Application Number
- CN202411691372.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-10
AI Technical Summary
Existing glass fiber reinforced thermoplastic composites are opaque due to light scattering and refraction, and their mechanical properties are degraded in humid and heat and ultraviolet radiation environments, limiting their use in applications requiring high intensity and high transparency.
Polyethylene terephthalate and polyethylene isophthalate are melt blended, polyadipyl isophthalamine and compatibilizer are added, and transparent weathering glass fiber reinforced are prepared by hot pressing treatment. Thermoplastic matrix composite material adjusts the refractive index and reduces the interfacial tension, improving the light transmittance and weather resistance of the material.
The composite material has high light transmittance (up to 89%), low haze (4.2%) and excellent mechanical properties, combining good optical transparency and weather resistance.
Smart Images

Figure BDA0005151043050000041 
Figure BDA0005151043050000061 
Figure BDA0005151043050000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a transparent weather-resistant glass fiber reinforced thermoplastic-based composite material and a preparation method thereof. Background Art
[0002] Glass fiber reinforced thermoplastic composite (GFRP) is an advanced composite material that uses glass fiber as a reinforcement and is tightly combined with a thermoplastic resin matrix. The composite material exhibits excellent properties such as light weight, high strength, excellent corrosion resistance and impact resistance, as well as good recyclability. These excellent properties have made GFRP widely used in many fields such as aerospace, automobile manufacturing, shipbuilding, architectural design, and electronic appliances.
[0003] Although GFRP is popular in the field of high-performance engineering, it is usually opaque due to the significant light scattering and refraction between the glass fiber and the polymer matrix. This limitation restricts its application in applications that require both high strength and high transparency. However, under harsh environmental conditions such as humidity, heat and ultraviolet radiation, the fiber-matrix bond in GFRP faces the risk of failure. This failure will not only lead to a decrease in the mechanical properties of the material, but will also further aggravate the light scattering and refraction, thereby significantly reducing its optical transparency.
[0004] In view of the defects and limitations of existing GFRP, it is necessary to study new methods to prepare glass fiber reinforced thermoplastic composites with excellent weather resistance and optical properties. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a transparent weather-resistant glass fiber reinforced thermoplastic-based composite material and a preparation method thereof.
[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0007] The present invention provides a method for preparing a transparent weather-resistant glass fiber reinforced thermoplastic-based composite material, comprising the following steps:
[0008] (1) respectively drying polyethylene terephthalate and polyethylene isophthalate, melt-blending them, and extruding them to prepare a polymer;
[0009] (2) drying and mixing the polymer prepared in step (1) and poly(m-xylylene adipamide) to obtain a mixture, adding a compatibilizer, melt blending, and compression molding to prepare a film;
[0010] (3) The film prepared in step (2) and the glass fiber material are alternately layered and then subjected to hot pressing to obtain a transparent weather-resistant glass fiber reinforced thermoplastic composite material.
[0011] Furthermore, during the melt blending in step (1), the content of polyethylene terephthalate (PETG) is 72.5wt% to 91.3wt%, and the content of polyethylene isophthalate (PEI) is 8.7wt% to 27.5wt%.
[0012] Furthermore, in the mixture obtained by melt blending in step (2), the content of the polymer is 76.2wt% to 97wt%, the content of poly(m-xylylene adipamide) (MXD6) is 3wt% to 23.8wt%; and the content of the added compatibilizer accounts for 20% of the total weight of the mixture.
[0013] Furthermore, the compatibilizer is one of p-toluenesulfonic acid, maleic anhydride graft copolymer, bifunctional epoxy resin and sodium sulfoisophthalate.
[0014] Preferably, in the mixture obtained by melt blending in step (2), the content of the polymer is 90wt%, the content of poly(m-phenylenediamine adipamide) is 10wt%, and the compatibilizer is sodium sulfoisophthalate.
[0015] The temperatures for melt blending in step (1) and step (2) are both 250-300°C.
[0016] Preferably, the temperature of melt blending in step (1) is 270°C.
[0017] Preferably, the temperature of melt blending in step (2) is 265°C.
[0018] The temperature of the compression molding in step (2) is 240-300° C., the pressure is 1-4 MPa, and the time is 2-10 min.
[0019] Preferably, the temperature of the compression molding in step (2) is 270° C., the pressure is 2.2 MPa, and the time is 4 min.
[0020] The temperature of the hot pressing treatment in step (3) is 240-300° C., the pressure is 2-7 MPa, and the time is 3-10 min.
[0021] Preferably, the temperature of the hot pressing treatment in step (3) is 260° C., the pressure is 5 MPa, and the time is 5 min.
[0022] The glass fiber material in step (3) is one of E-glass fiber, C-glass fiber, S-glass fiber and AR-glass fiber.
[0023] Preferably, the glass fiber material in step (3) is E-glass fiber, corresponding to a tensile strength of 2200 MPa and a thickness of 0.12 mm.
[0024] The drying temperature in step (1) and step (2) is 50-100°C.
[0025] Preferably, in step (1), the drying temperature of PETG is 80°C, and the drying temperature of PEI is 60°C.
[0026] Preferably, the drying temperature of the polymer and MXD6 in step (2) is 80°C.
[0027] The present invention also provides a transparent weather-resistant glass fiber reinforced thermoplastic-based composite material prepared by the above preparation method.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention reduces the intrinsic birefringence of the PETG matrix by partially replacing polyethylene terephthalate (PETG) with polyethylene isophthalate (PEI). The PEI substitution destroys the arrangement of the PETG chain, thereby reducing the refractive index anisotropy and improving the opaque property of GFRP. By melt copolymerizing poly(m-phenylene adipamide) (nylon MXD6) with excellent weather resistance and polyethylene terephthalate (PETG), the refractive index (RI) value thereof is adjusted to match the glass fiber, and the weather resistance thereof is improved. By adding a compatibilizer, the interfacial tension between different structures is reduced, the structural size of MXD6 is reduced, and the thermodynamics matching is achieved.
[0030] The transparent weather-resistant glass fiber reinforced thermoplastic-based composite material prepared by the present invention has a maximum light transmittance of 89%, a haze of 4.2%, a heat shrinkage of 1.1%, and a tensile strength of 405 MPa, and has high optical transparency, good weather resistance and excellent mechanical properties. DETAILED DESCRIPTION
[0031] The following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0032] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, components and / or combinations thereof. The experimental methods in the following examples that do not specify specific conditions are all based on conventional techniques in the art, or according to the conditions recommended by the manufacturer; the reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0033] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific examples.
[0034] Example 1
[0035] A method for preparing a transparent weather-resistant glass fiber reinforced thermoplastic-based composite material comprises the following steps:
[0036] (1) 80 wt% of polyethylene terephthalate (PETG) was vacuum dried at 80°C for 48 h, and 20 wt% of polyethylene isophthalate (PEI) was vacuum dried at 60°C for 48 h, and melt-blended using a twin-screw extruder at a speed of 100 rpm and a drum temperature of 270°C for 4 min. The molten mixture was extruded through a die to prepare particles, thereby obtaining a polymer;
[0037] (2) 90 wt % of a polymer and 10 wt % of poly(m-xylylene adipamide) (MXD6) were vacuum dried at 80° C. for 24 h, mixed to obtain a mixture, 20 wt % of sodium sulfoisophthalate compatibilizer accounting for the total weight of the mixture was added, melt blended in a twin-screw extruder, and then compression molded at 270° C. and 2.2 MPa for 4 min to prepare a PETG / MXD6 film;
[0038] (3) The prepared film and E-glass fiber material with a thickness of 0.12 mm and a tensile strength of 2200 MPa are alternately layered, and then placed in a vacuum hot press and hot-pressed at 260°C and 5 MPa for 5 min to obtain a transparent weather-resistant glass fiber reinforced thermoplastic matrix composite material.
[0039] Example 2
[0040] The preparation method of Example 2 is substantially the same as that of Example 1, except that in step (2), the content of the polymer in the mixture is 88.2 wt %, and the content of MXD6 is 11.8 wt %.
[0041] Example 3
[0042] The preparation method of Example 3 is substantially the same as that of Example 1, except that in step (2), the content of the polymer in the mixture is 82.5 wt %, and the content of MXD6 is 17.5 wt %.
[0043] Example 4
[0044] The preparation method of Example 4 is substantially the same as that of Example 1, except that in step (2), the content of the polymer in the mixture is 79 wt %, and the content of MXD6 is 21 wt %.
[0045] Example 5
[0046] The preparation method of Example 5 is substantially the same as that of Example 1, except that in step (2), the content of the polymer in the mixture is 91.6 wt %, and the content of MXD6 is 8.4 wt %.
[0047] Example 6
[0048] The preparation method of Example 6 is substantially the same as that of Example 1, except that in step (2), the content of the polymer in the mixture is 95 wt %, and the content of MXD6 is 5 wt %.
[0049] Performance Testing
[0050] The performance test indicators of the glass fiber reinforced thermoplastic matrix composite material of the present invention include light transmittance, haze, tensile properties and thermal shrinkage, and the specific test methods are as follows:
[0051] (1) Light transmittance test: According to the current national standard GB / T 2410-2008, the light transmittance of glass fiber reinforced thermoplastic matrix composite materials was measured at a wavelength of 400nm-800nm using an ultraviolet-visible spectrophotometer, and the maximum light transmittance at each wavelength was taken as the light transmittance of the glass fiber reinforced thermoplastic matrix composite materials.
[0052] (2) Haze test: The haze of glass fiber reinforced thermoplastic composites was measured using a WGT-S haze tester in accordance with the current national standard GB / T 2410-2008.
[0053] (3) Tensile property test: The tensile properties of glass fiber reinforced thermoplastic matrix composites were tested according to ISO527-1 test standard, with a tensile rate of 50 mm / min.
[0054] (4) Thermal shrinkage test: The thermal shrinkage of glass fiber reinforced thermoplastic composite materials was tested under heating conditions of 150°C for 30 min in accordance with the current national standard GB / T 18374-2008.
[0055] The above performance tests were performed on Examples 1 to 6, and the test results are shown in Table 1.
[0056] Table 1 Properties of glass fiber reinforced thermoplastic composite materials of Examples 1 to 6
[0057]
[0058] It can be seen from Table 1 that when the MXD6 content is within 10wt%, the transmittance of GFRP gradually increases with the increase of MXD6 content, and the haze gradually decreases with the increase of MXD6 content. When the MXD6 content is 10wt%, the transmittance reaches a maximum of 89% and the haze reaches a minimum of 4.2%, indicating that the glass fiber reinforced thermoplastic matrix composite material prepared by the present invention has excellent optical properties. This is because as the MXD6 content increases, the refractive index of PETG / MXD6 as a polymer matrix matches that of the glass fiber, effectively reducing light scattering and light refraction; further increasing the MXD6 content, the transmittance gradually decreases and the haze gradually increases. This is because when the MXD6 addition amount is too high, the difference between the matrix refractive index and the dispersed phase refractive index increases, resulting in an increase in the haze of the blend and a decrease in the transmittance. In addition, the tensile strength of the composite materials of Examples 1 to 6 is relatively high, the elongation at break is relatively low, and the thermal shrinkage of the panels is still relatively low when heated at 150°C for 30 min, which indicates that the glass fiber reinforced thermoplastic-based composite materials prepared by the present invention have excellent mechanical properties and weather resistance.
[0059] Comparative Example 1
[0060] The preparation method of Comparative Example 1 is substantially the same as that of Example 1, except that in step (2), the content of the polymer in the mixture is 100 wt %, and the content of MXD6 is 0.
[0061] Comparative Example 2
[0062] The preparation method of Comparative Example 2 is substantially the same as that of Example 1, except that in step (2), the content of the polymer in the mixture is 0, and the content of MXD6 is 100 wt%.
[0063] The composite materials prepared in Comparative Examples 1 and 2 were tested for performance, and the results are shown in Table 2.
[0064] Table 2 Performance of glass fiber reinforced thermoplastic composite materials of comparative examples 1 to 2
[0065] Detection parameters Example 1 Comparative Example 1 Comparative Example 2 Polymer (wt%) 90 100 0 MXD6 (wt%) 10 0 100 Plate thickness (mm) 0.44 0.44 0.44 Glass fiber content of board (wt%) 42.0 41.7 41.5 Haze(%) 4.2 15.8 24 Tensile strength(MPa) 405 272 255 Elongation at break (%) 2.3 3.0 1.9 Light transmittance (%) 89 73.6 55.3 Thermal shrinkage (%) 1.1 1.1 1.2
[0066] As shown in Table 2, when the polymer or MXD6 is used alone to prepare the film, the light transmittance of the composite material is significantly reduced, the haze is significantly increased, and the optical performance is significantly reduced. This is because the melt copolymerization of the polymer and MXD6 can adjust the refractive index to match the glass fiber and improve the optical properties of the composite material.
[0067] Comparative Example 3
[0068] The preparation method of Comparative Example 1 is substantially the same as that of Example 1, except that step (1) is omitted and the polymer is replaced by PETG in step (2).
[0069] The composite material prepared in Comparative Example 3 was tested for performance, and the results are shown in Table 3.
[0070] Table 3 Performance of glass fiber reinforced thermoplastic composite material of comparative example 3
[0071] Detection parameters Example 1 Comparative Example 3 PEI (wt%) 20 0 PETG (wt%) 80 100 Plate thickness (mm) 0.44 0.43 Glass fiber content of board (wt%) 42.0 42.0 Haze(%) 4.2 18.7 Tensile strength(MPa) 405 355 Elongation at break (%) 2.3 2.5 Light transmittance (%) 89 70.5 Thermal shrinkage (%) 1.1 1.2
[0072] As shown in Table 3, the light transmission effect and haze of melt copolymerization of PETG and MXD6 without PEI substitution are inferior to those of Example 1. This is because PEI substitution destroys the arrangement of PETG chains, thereby reducing the refractive index anisotropy and improving the opaque property of GFRP.
[0073] Comparative Example 4
[0074] The preparation method of Comparative Example 4 is substantially the same as that of Example 1, except that in step (2), MXD6 in the mixture is replaced by polyamide 6, the content of the polymer is 91.2 wt %, and the content of the polyamide 6 is 8.9 wt %.
[0075] Comparative Example 5
[0076] The preparation method of Comparative Example 5 is substantially the same as that of Example 1, except that in step (2), MXD6 in the mixture is replaced by polyamide 6, the content of the polymer is 89 wt %, and the content of the polyamide 6 is 11 wt %.
[0077] Comparative Example 6
[0078] The preparation method of Comparative Example 6 is substantially the same as that of Example 1, except that in step (2), MXD6 in the mixture is replaced by polyamide 6, the content of the polymer is 81.6 wt %, and the content of the polyamide 6 is 18.4 wt %.
[0079] Comparative Example 7
[0080] The preparation method of Comparative Example 7 is substantially the same as that of Example 1, except that in step (2), MXD6 in the mixture is replaced by polyamide 6, the content of the polymer is 100 wt %, and the content of the polyamide 6 is 0.
[0081] Comparative Example 8
[0082] The preparation method of Comparative Example 8 is basically the same as that of Example 1, except that in step (2), MXD6 in the mixture is replaced by polyamide 6 (nylon 6), the polymer content is 0, and the polyamide 6 content is 100 wt%.
[0083] The composite materials prepared in Comparative Examples 4 to 8 were tested for performance, and the results are shown in Table 4.
[0084] Table 4 Performance of glass fiber reinforced thermoplastic composite materials of comparative examples 4 to 8
[0085]
[0086]
[0087] It can be seen from Table 4 that when nylon 6 is used to replace MXD6 and melt-blended with the polymer, the light transmittance of the composite material is reduced, the haze is increased, and the optical performance is reduced compared with Example 1. At the same time, the tensile strength of the composite material is reduced, and the mechanical properties are reduced, indicating that the effect of the composite material combined with MXD6 and the polymer is better.
[0088] Comparative Example 9
[0089] The preparation method of Comparative Example 9 is substantially the same as that of Example 1, except that in step (2), MXD6 in the mixture is replaced by polyhexamethylene adipamide, the content of the polymer is 94 wt %, and the content of the polyhexamethylene adipamide is 6 wt %.
[0090] Comparative Example 10
[0091] The preparation method of Comparative Example 10 is substantially the same as that of Example 1, except that in step (2), MXD6 in the mixture is replaced by polyhexamethylene adipamide, the content of the polymer is 89.5 wt %, and the content of the polyhexamethylene adipamide is 10.5 wt %.
[0092] Comparative Example 11
[0093] The preparation method of Comparative Example 11 is substantially the same as that of Example 1, except that in step (2), MXD6 in the mixture is replaced by polyhexamethylene adipamide, the content of the polymer is 84 wt %, and the content of the polyhexamethylene adipamide is 16 wt %.
[0094] Comparative Example 12
[0095] The preparation method of Comparative Example 12 is substantially the same as that of Example 1, except that in step (2), MXD6 in the mixture is replaced by polyhexamethylene adipamide, the content of the polymer is 78.7 wt %, and the content of the polyhexamethylene adipamide is 21.3 wt %.
[0096] Comparative Example 13
[0097] The preparation method of Comparative Example 13 is basically the same as that of Example 1, except that in step (2), MXD6 in the mixture is replaced by polyhexamethylene adipamide, the content of the polymer is 100wt%, and the content of the polyhexamethylene adipamide is 0.
[0098] Comparative Example 14
[0099] The preparation method of Comparative Example 14 is basically the same as that of Example 1, except that in step (2), MXD6 in the mixture is replaced by polyhexamethylene adipamide, the content of the polymer is 0, and the content of polyhexamethylene adipamide is 100 wt%.
[0100] The composite materials prepared in Comparative Examples 9 to 14 were tested for performance, and the results are shown in Table 5.
[0101] Table 5 Performance of glass fiber reinforced thermoplastic composite materials of comparative examples 9 to 14
[0102]
[0103] It can be seen from Table 5 that when polyhexamethylene adipamide is used instead of MXD6 to be melt-blended with the polymer, the light transmittance of the composite material is reduced, the haze is increased, and the optical properties are reduced compared with Example 1. At the same time, the tensile strength of the composite material is reduced, and the mechanical properties are reduced, indicating that the effect of the composite material combined with MXD6 and the polymer is better.
[0104] The above description is only a preferred embodiment of the present invention, but is not limited to the above examples. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a transparent weather-resistant glass fiber reinforced thermoplastic-based composite material, characterized in that: The following steps are involved: (1) respectively drying polyethylene terephthalate and polyethylene isophthalate, melt-blending them, and extruding them to prepare a polymer; (2) drying and mixing the polymer prepared in step (1) and poly(m-xylylene adipamide) to obtain a mixture, adding a compatibilizer, melt blending, and compression molding to prepare a film; (3) The film prepared in step (2) and the glass fiber material are alternately layered and then subjected to heat pressing to obtain a transparent weather-resistant glass fiber reinforced thermoplastic composite material.
2. The preparation method according to claim 1, characterized in that: During the melt blending in step (1), the content of polyethylene terephthalate is 72.5wt% to 91.3wt%, and the content of polyethylene isophthalate is 8.7wt% to 27.5wt%.
3. The preparation method according to claim 2, characterized in that: In the mixture obtained by melt blending in step (2), the content of the polymer is 76.2wt% to 97wt%, the content of poly(m-xylylene adipamide) is 3wt% to 23.8wt%; and the content of the added compatibilizer accounts for 20% of the total weight of the mixture; The compatibilizer is one of p-toluenesulfonic acid, maleic anhydride graft copolymer, bifunctional epoxy resin and sodium sulfoisophthalate.
4. The preparation method according to claim 3, characterized in that: In the mixture obtained by melt blending in step (2), the content of the polymer is 90wt%, and the content of poly(m-xylylene adipamide) is 10wt%.
5. The preparation method according to claim 1, characterized in that: The temperatures for melt blending in step (1) and step (2) are both 250-300°C.
6. The preparation method according to claim 5, characterized in that: The temperature of the compression molding in step (2) is 240-300° C., the pressure is 1-4 MPa, and the time is 2-10 min.
7. The preparation method according to claim 6, characterized in that: The temperature of the hot pressing treatment in step (3) is 240-300° C., the pressure is 2-7 MPa, and the time is 3-10 min.
8. The preparation method according to claim 3, characterized in that: The glass fiber material in step (3) is one of E-glass fiber, C-glass fiber, S-glass fiber and AR-glass fiber.
9. The preparation method according to claim 1, characterized in that: The drying temperatures in step (1) and step (2) are both 50-100°C.
10. A transparent weather-resistant glass fiber reinforced thermoplastic-based composite material prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Thermoplastic transparent glass fiber composite board, preparation method thereof and production device of composite board
CN120697286A